Minat Berwirausaha Pada Gen-Z di Era Digital - Rahmadiane, Ghea Dwi; Harjanti, Ririh Sri (Owner : Riset dan Jurnal Akuntansi, 2024)
The current interest in entrepreneurship was a solution to the problem of the large number of human resources that cannot yet be fully absorbed by existing employment opportunities. This is a challenge in itself, especially for universities, to ascertain what factors can influence existing programs so that they can be strengthened. Moreover, students currently fall into the Generation Z category, which has the characteristics of being more careful and with a long-term perspective. The objectives of this research include finding out the role of entrepreneurial literacy, income expectations, and digital literacy. The population in this study are active students in Indonesia, seen in the Higher Education Data Base (PDDikti) statistical data of 6,028,003 students. Meanwhile, the sample size in this study was calculated using the Slovin Formula at an error rate of 5%, obtained at 400 students. The sampling technique used is Simple Random Sampling. The data in this research uses quantitative data sourced from primary data in the form of tabulated results from questionnaires distributed. The analytical method in this research used multiple regression analysis. The results of the calculation of variable X1 obtained tcount of 4.408 > t table and a significant value of 0.000 < 0.05, variable significant value of 0.004 <0.05. This shows that the influence of entrepreneurial literacy, income expectations, digital literacy on entrepreneurial interest.